2024
DOI: 10.1155/2024/8816919
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of Rheumatoid Arthritis by Inducing IDO Expression with Trichinella spiralis Recombinant Protein 43

Xiao Ma,
Dongming Liu,
Wenhao Yu
et al.

Abstract: Rheumatoid arthritis (RA) represents the autoimmune disorder that shows aggressive arthritis as the main symptom. It is difficult to treat and can lead to joint deformation and function loss. At present, Trichinella spiralis (T. spiralis) antigen has attracted much attention because it plays a role in host immune regulatory mechanisms. Therefore, we selected T. spiralis recombinant protein 43 (Tsp43) to treat the bovine collagen type II (BCII)-induced mice RA model and explored its therapeutic mechanisms. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Tatara et al demonstrated that BM-MSCs can inhibit the proliferation of Th17, partially acting through prostaglandin E2 (PGE2) and indoleamine 2,3-dioxygenase (IDO); however, they did not influence Tregs [ 95 ]. As IDO is an important enzyme responsible for tryptophan metabolism, its increased concentration leads to impaired function and promotes apoptosis in T cells [ 96 ]. The crucial role of IDO and IL-10 in the immunosuppressive activity of MSCs has been confirmed in a study in which BM-MSCs from healthy donors were epigenetically modified to have upregulated IDO and IL-10 expressions.…”
Section: Mesenchymal Stromal Cells and T Cellsmentioning
confidence: 99%
“…Tatara et al demonstrated that BM-MSCs can inhibit the proliferation of Th17, partially acting through prostaglandin E2 (PGE2) and indoleamine 2,3-dioxygenase (IDO); however, they did not influence Tregs [ 95 ]. As IDO is an important enzyme responsible for tryptophan metabolism, its increased concentration leads to impaired function and promotes apoptosis in T cells [ 96 ]. The crucial role of IDO and IL-10 in the immunosuppressive activity of MSCs has been confirmed in a study in which BM-MSCs from healthy donors were epigenetically modified to have upregulated IDO and IL-10 expressions.…”
Section: Mesenchymal Stromal Cells and T Cellsmentioning
confidence: 99%